Use of gemtuzumab ozogamycin combined with conventional chemotherapy in patients with acute myeloid leukemia - Perini,Guilherme Fleury (2011)
Objective: To analyze the outcome of patients treated with gemtuzumab ozogamycin combined with conventional therapy treated at Hospital Israelita Albert Einstein. Methods: 14 patients who had high risk features (secondary leukemia, unfavorable cytogenetics, and refractory disease) were treated with gemtuzumab ozogamycin combined with conventional therapy and their outcome was analysed by reviewing their medical records. Results: Overall response rate was 58%, with 43% achieving complete response, with a median follow-up of 11 months, event-free survival was 3 months. Eleven patients died, 6 of them due to refractory acute myeloid leukemia. Only four patients presented with grade 3 to 4 toxicities and only one patient had sinusoidal obstruction syndrome after bone marrow transplant. Conclusion: gemtuzumab ozogamycin combined with chemotherapy is a feasible treatment regimen in acute myeloid leukemia patients. However, further studies are necessary to clarify which subgroup of patients may beneft from this treatment.